Healthcare Service Provisions for Foreign Travellers: A Case of Thailand - Manatee Jitanan; Shuaibu Saidu Musa; Pornchan Lojanasupareuk (Public Health Challenges)
Abstract Thailand is a major tourist destination in the world and attracts millions of people every year because of its pleasant weather, varied cuisine, hospitality and a good economy. However, Thailand's visitors may be exposed to various health risks. Among them, food poisoning particularly from the country's famous spicy cuisine, and respiratory problems caused by the pollution of particles, particularly in areas such as Chiang Mai. Sexually transmitted diseases (STDs) such as HIV/AIDS and hepatitis are more likely to be transmitted during non‐protected sexual behaviour. In addition, road traffic accidents are often exacerbated by alcohol consumption at festivals and are of considerable risk. Despite these health risks, Thailand's healthcare system is supported by a universal health insurance policy that offers affordable and accessible medical treatment for travellers, such as dental healthcare and telemedicine options. Medical tourism is also widespread, with Thai cosmetic surgery and herbal treatments becoming increasingly popular among tourists. These medical facilities help reduce the impact of health risks and ensure travellers get the care they need during their stay in Thailand.